Addiction Rehabilitation and Structural Family Therapy - Shoup, Raymond; Baranovich, Diana Lea (Institute of Medico-Legal Publications, 2019)
Addiction is a societal problem that has affected people from all over the world. As this is the case, a serious look needs to be taken with regards to treatment. Structural Family Therapy was fathered by Salvador Minuchin, who believed that addictions in the family causes a shift in the dynamic of the family, which is where addiction rehabilitation treatment with family members affected by addictions should begin. When working with clients who have addictions, it is important to view the client through a holistic lens; meaning we must view how the substances/activities, and the stresses in their lives which led them to the substances/activities, cause changes in their psychology and physiology. From there, we can create a treatment plan that works with families that offers a prognosis for the client’s life, not just treating their addiction. Structural Family Therapy is great for this, has part of treatment is looking at the client holistically, and helping heal the various parts of the clients lives, including healing their family unit. © 2019, Indian Journal of Public Health Research and Development. All right reserved.